Programmed death-1 (PD-1) receptor/PD-1 ligand (PD-L1) expression in fumarate hydratase-deficient renal cell carcinoma - Alaghehbandan, Reza; Stehlik, Jan; Trpkov, Kiril; Magi-Galluzzi, Cristina; Condom Mundo, Enric; Pane Foix, Maria; Berney, Daniel; Sibony, Mathilde; Suster, Saul; Agaimy, Abbas; Montiel, Delia Perez; Pivovarcikova, Kristyna; et al. (Annals of diagnostic pathology, 2017)
Fumarate hydratase-deficient renal cell carcinoma (FH-RCC) is a rare and aggressive tumor affecting mostly younger patients. This is the first study to assess the expression of programmed death-1 (PD-1) receptor/PD-1 ligand (PD-L1) in FH-RCC. Formalin-fixed paraffin-embedded samples from 13 FH-RCCs collected in an international multi-institutional study, were evaluated by immunohistochemistry (IHC) for PD-1/PD-L1 reactivity in tumor cells and tumor infiltrating lymphocytes (TILs). PD-1/PD-L1 expression was further evaluated by qPCR. By IHC, PD-1 was negative in tumor cells in all 13 cases. PD-L1 was positive in tumor cells in 2/13 cases, weak positive in 7/13, and negative in 4/13 cases, respectively. In TILs, PD-1 was positive in 1/13, weak positive in 3/13, and negative in 9/13 cases. In TILs, PD-L1 was weak positive by IHC in 5/13, and negative in 8/13 cases, respectively. qPCR confirmed the result for 2 of 3 IHC weak positive PD-1 samples. Of 7 IHC weak positive samples (in tumor cells), PD-L1 mRNA was detected in all 7 tumors. The majority of FH-RCCs did not express PD-1/PD-L1 by IHC, which was confirmed by molecular analysis. PD-1/PD-L1 expression in FH-RCC is restricted to a proportion of cases which may benefit from targeted therapies.
Keywords: nádory ledvin; Humans; lidé středního věku; PD-1 ligand (PD-L1) receptor; Fumarate hydratase-deficient renal cell carcinoma; Female; fumarasa; dospělí; Kidney; antigeny CD279; lidé; Fumarate Hydratase; Immunohistochemistry; přežití bez známek nemoci; B7-H1 Antigen; imunohistochemie; Lymphocytes, Tumor-Infiltrating; Adult; ženské pohlaví; Male; Middle Aged; tumor infiltrující lymfocyty; karcinom z renálních buněk; Disease-Free Survival; Carcinoma, Renal Cell; antigeny CD274; mužské pohlaví; Programmed Cell Death 1 Receptor; Programmed death-1 (PD-1) receptor; Kidney Neoplasms